The Dynamics of Vehicles Basics, Simulation and Autonomous Systems - Turan Arat, Hüseyin (IntechOpen, 2023)
This book provides information about the fundamentals of vehicle dynamics, modeling, simulation, and autonomous vehicles. It discusses vehicle dynamics steps to consider when modeling a vehicle and the effects of vehicle dynamics in hybrid, electric, and autonomous vehicles.